PERIPHERAL SETTLEMENTS OF CONCHOPATA URBAN CENTER, AYACUCHO - Pérez Calderón, Ismael (2012)
Provides information on a variety of archaeological remains on the periphery of downtown Conchopata in Ayacucho, which is demonstrated not only a long occupation but an urban pattern with a background in local cultures prior to the Wari culture. He has logged more than 200 settlements distributed between 2500 and 4250 masl, whose ancient people made the most of natural resources in the area as well as the domain of geographic space, between the evidence include quarries, docks, canals, reservoirs, qochas, springs, settlements, rock art, caves, temples, huancas, ushnos, roads, etc., scattered on top of hills, creeks, hills, slopes, plains and deep gorges that make up the upper basin in southern highlands Huarpa central Peruvian Andes.